Si-based Anode Lithium-Ion Batteries: A Comprehensive Review of Recent Progress - Li, Yifei; Li, Qingmeng; Chai, Jiali; Wang, Yiting; Du, Jiakai; Chen, Zhiyuan; Rui, Yichuan; Jiang, Lei; Tang, Bohejin (ACS materials letters, 2023)
Si-based anode materials offer significant advantages, such as high specific capacity, low voltage platform, environmental friendliness, and abundant resources, making them highly promising candidates to replace graphite anodes in the next generation of high specific energy lithium-ion batteries (LIBs). However, the commercialization of Si-based anodes for LIBs encounters significant barriers due to inherent challenges. These challenges encompass a range of issues, including poor electrical conductivity, substantial volume expansion during the lithiation–delithiation process, severe pulverization of the electrodes, pronounced thickening of the solid electrolyte interphase film, low Coulombic efficiency, and limited cycling performance. Each of these factors leads to the complexity of realizing the full potential of Si-based anodes in commercial LIBs applications. This review provides a comprehensive summary and discussion of recent research on Si-based LIB anodes, focusing on the microscopic morphology of Si and the development of Si-based composite materials. By offering a novel perspective, this review aims to provide an overview and insightful discussion of Si-based anodes. The latest research findings are presented, and innovative viewpoints and reasonable insights are addressed, shedding light on the potential solutions to overcome the limitations associated with Si-based anodes.